TINGKAT PENERIMAAN KONSUMEN TERHADAP MINUMAN HERBAL TEH DAUN SIRSAK (Annona muricata Linn.) - Nathania E. Ong; Gregoria S. S. Djarkasi; Judith C. S. Moningka (COCOS, 2016)
ABSTRACTSoursop leaves tea is an herbal tea that has a distinctive flavor and distinct from the other leaves. The aim of this research is to determine the level of consumer acceptance of soursop leaves herbal tea. The research arranged using Factorial Completely Randomized Design with 3 factors, processing, leaves of processed form, and long extraction. Analysis of consumer acceptance include taste, color, and aroma of soursop leaves herbal tea. The hedonic test of soursop leaves tea with the highest score of taste, color and aroma is sample on boiled extraction method, with flakes leaves, and 7 minutes of long extraction.Keywords : soursop, herbal tea, hedonic test